Using rambutan leaves (nephelium lappaceum l.) as hair done in hair dye preparations - Dill Sastia Mara; Doni Saputra Pasaribu (Science Midwifery, 2022)
The use of natural hair dyes is a solution to changing hair color such as gray hair. Rambutan leaves can be used as a natural hair dye, because rambutan leaves contain tannins and saponins, tannins can produce yellow, brown to golden colors. To formulate the simplex powder of rambutan leaves (Nephelium lappaceum L.) with various concentrations as a hair blackener with the additional ingredients pyrogallol and copper (II) sulfate. The dried rambutan leaves were made into powder, sifted through a 100 mesh sieve. The hair dye preparation was made with a formula consisting of rambutan leaf powder (Nephelium lappaceum L.) with various concentrations, namely formula F1 2.5%, formula F2 5%, formula F3 7.5%, formula F4 10%, with additional ingredients pyrogallol 1%, copper (II) sulfate 1%, and xanthan gum 0.5%. Water is used as a solvent. Staining is done by soaking gray hair in a hair dye preparation for 1-4 hours and observing the color change visually every hour. Then an evaluation test was carried out to evaluate the stability of the color against washing, sun exposure and irritation test on the skin with the selected formula. After soaking gray hair for 4 hours in hair dye, formula F1 gives a medium brown color, formula F2 gives a medium black color, formula F3 gives light black color and the F4 formula gives a dark brown color. The results of the evaluation test using the F2 formula showed that the resulting colors were stable at 1, 5, 10, and 15 washings, stable against sun exposure and did not cause irritation to the skin. Rambutan leaf powder (Nephelium lappaceum L.) with the additional ingredients pyrogallol and copper (II) sulfate can be formulated into hair dye preparations and gives a black color at a concentration of 5% rambutan leaf powder (formula F2).